Astor eaudiobook The rise and fall of an american fortune. - Cooper, Anderson (HarperAudio, 2023)
The number one New York Times bestselling authors of Vanderbilt return with another riveting history of a legendary American family, the Astors, and how they built and lavished their fortune. The story of the Astors is a quintessentially American story—of ambition, invention, destruction, and reinvention. From 1783, when German immigrant John Jacob Astor first arrived in the United States, until 2009, when Brooke Astor's son, Anthony Marshall, was convicted of defrauding his elderly mother, the Astor name occupied a unique place in American society. The family fortune, first made by a beaver trapping business that grew into an empire, was then amplified by holdings in Manhattan real estate. Over the ensuing generations, Astors ruled Gilded Age New York society and inserted themselves into political and cultural life, but also suffered the most famous loss on the Titanic, one of many shocking and unexpected twists in the family's story. In this unconventional, page-turning historical biography, #1 New York Times bestselling authors Anderson Cooper and Katherine Howe chronicle the lives of the Astors and explore what the Astor name has come to mean in America—offering a window onto the making of America itself. Supplemental enhancement PDF accompanies the audiobook.